2013
DOI: 10.1126/science.1242321
|View full text |Cite
|
Sign up to set email alerts
|

Phycobilisomes Supply Excitations to Both Photosystems in a Megacomplex in Cyanobacteria

Abstract: In photosynthetic organisms, photons are captured by light-harvesting antenna complexes, and energy is transferred to reaction centers where photochemical reactions take place. We describe here the isolation and characterization of a fully functional megacomplex composed of a phycobilisome antenna complex and photosystems I and II from the cyanobacterium Synechocystis PCC 6803. A combination of in vivo protein cross-linking, mass spectrometry, and time-resolved spectroscopy indicates that the megacomplex is or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
241
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(261 citation statements)
references
References 55 publications
10
241
4
1
Order By: Relevance
“…This protrusion fits well with the hole on the cytoplasmic side of PSII and forms a tight interaction between PBS and PSII, which is likely required for an efficient energy transfer from PBS to PSII. The tight association between PBS and PSII agrees with a recent report that demonstrated the formation of the PBS-PSII-PSI megacomplex in vivo via protein cross-linking and mass spectrometry analyses [27]. It should also be noted that EM imaging showed peripheral rods attached to the bottom of the cores of PBSs isolated from the ∆apcF mutant ( Figure 4C).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This protrusion fits well with the hole on the cytoplasmic side of PSII and forms a tight interaction between PBS and PSII, which is likely required for an efficient energy transfer from PBS to PSII. The tight association between PBS and PSII agrees with a recent report that demonstrated the formation of the PBS-PSII-PSI megacomplex in vivo via protein cross-linking and mass spectrometry analyses [27]. It should also be noted that EM imaging showed peripheral rods attached to the bottom of the cores of PBSs isolated from the ∆apcF mutant ( Figure 4C).…”
Section: Discussionsupporting
confidence: 77%
“…Early reports showed that state transitions occurred in a time range of subseconds to seconds [25] and that this process is controlled by the redox state of electron carriers between PSI and PSII [26]. Liu et al [27] recently reported the isolation of a PBS-PSII-PSI mega-complex, and suggested that PBS does not need to change its spatial position during state transitions. In this study, we investigated the three-dimensional (3D) structures of the intact PBS and PBS-PSII complexes from Anabaena 7120 using single-particle electron microscopy (EM) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 shows that, using a different method to immobilize membranes, PSII complexes can be imaged at low resolution, and they likely sit alongside PSI complexes. The mixed PSI/PSII T. elongatus membranes identified in Figures 5A and 5B, and those from Synechocystis ( Figure 7) and Synechococcus 7002 (Supplemental Figure 10) could be the origin of the megacomplex consisting of PSI, PSII, and a phycobilisome (Liu et al, 2013); the PSI-PSII contact zones shown in this work could provide sites for docking phycobilisomes, which are then proposed to donate excitation energy to either one of these photosystems (Liu et al, 2013). The regions with PSI and PSII in close proximity in Figures 5A and 5B also create the conditions for "spillover" of excitations from PSII to PSI (Biggins and Bruce, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Orange carotenoid protein (OCP) is a specific 35 kDa watersoluble protein that plays an essential role in non-photochemical quenching (NPQ) of the cyanobacterial light-harvesting antennae, phycobilisomes (1)(2)(3)(4). OCP acts as a blue-green light intensity sensor (5).…”
Section: Introductionmentioning
confidence: 99%